PF-33 Effects of GnRH Vaccine, Improvac®, on Oestrus, Ovarian Activity and Growth in Japanese Black Fattening Beef Heifers - Leni Sri Lestari; Keita Kitagawa; Misato Tsugeuma; Masahiko Kibushi; Yoshihiro Deguchi; Mina Shirotozaki; Ryo Sasahara; Sintaro Tau; Hiromichi Tamada; Noritoshi Kawate (Hemera Zoa, 2018)
Introduction Oestrus and mounting behaviors in female beef herds often lead to damage of carcass and reduction of feed intake. Gonadotropin releasing hormone (GnRH) vaccine suppresses gonadal functions in cattle, neutralize biological activity of endogenous GnRH by raising GnRH antibody. This method has been used as chemical castrations of young bulls and cows in several overseas countries. However, there have been no reports regarding effects of GnRH vaccine on gonadal functions of Japanese black fattening beef heifers. The present study was conducted to examine effects of Improvac®, a GnRH vaccine, on oestrus behavior, ovarian activity and growth in Japanese black fattening beef heifers.